A novel colorimetric and fluorescent probe for detecting fluoride anions: from water and toothpaste samples. Issue 2 (14th January 2016) - Yu, Mingming; Xu, Jie; Peng, Chao; Li, Zhanxian; Liu, Chunxia; Wei, Liuhe
Abstract: Based on 8-hydroxyquinoline, a 1, 8-naphthalimide-derived colorimetric and fluorescent probe was synthesized for naked-eye and fluorescent recognition of F − (from both tetrabutylammonium fluoride and NaF) with high sensitivity and excellent selectivity. The probe can be employed to detect F − quantitatively within certain concentration range, and the detection limit could be as low as 1.8 μM for tetrabutylammonium fluoride and 9 μM for NaF. With this probe, the tests for fluorine contents in tap water, water sample from Eyebrow Lake and several brands of toothpastes were successfully performed. Graphical abstract: Based on 8-hydroxyquinoline, a 1, 8-naphthalimide-derived probe was synthesized for F − (from tetrabutylammonium fluoride and NaF) naked-eye and fluorescent recognition with high sensitivity and excellent selectivity, the detection limit could be as low as 1.8 μM for tetrabutylammonium fluoride and 9 μM for NaF.